Extranodal NK/T-cell lymphoma-nasal type: Experience from a regional cancer center in India - Smitha Carol Saldanha; Pravin Ashok Khandare; Lokanatha Dasappa; Linu Abraham Jacob; M C Suresh Babu; K N Lokesh; M N Suma (Wolters Kluwer Medknow Publications, 2020)
Introduction: Extranodal natural killer/T-cell lymphoma-nasal type (ENKTL-NT) is an aggressive rare non-Hodgkin's lymphoma (NHL) subtype. It presents with involvement of the nasal and upper aerodigestive region causing extensive destruction of these midline structures. It has a predilection for the Asian population. Most cases present in the early-stage disease. Treatment outcomes are usually poor, and no consensus for optimal treatment strategy exists. Patients and Methods: This is a retrospective analysis of ENKTL-NT, diagnosed in a regional cancer center in India during the period of 2013-2018. The demographic and clinical features, laboratory parameters, radiological, histopathological features, and treatment outcomes were studied. Patients were treated with SMILE or AspaMetDex regimes sandwiched with radiotherapy. Statistical analysis was performed using software "Epi Info" Version 7.2, (CDC, Atlanta, Georgia, USA). Results: Fourteen patients were diagnosed with ENKTL-NT during this period. Eight patients received SMILE, and six patients have received AspaMetDex as induction chemotherapy. Ten (71.42%) of 14 patients have achieved CR. At the median follow-up of 30 months (4-47 months), nine patients relapsed with median progression-free survival of 22 months. The median overall survival was not reached. There were two induction deaths, one in AspaMetDex and one in the SMILE group. All patients receiving SMILE experienced at least one episode of Grade 3/4 hematological toxicity. Patients receiving AspaMetDex did not have any Grade 3/4 hematological toxicity. Discussion: ENKTL-NT in India is not as common as reported in other Asian countries. Patients usually present at an earlier stage because of the peculiar site of affection. It has high response rates, but relapses are common. Most of the relapses occur within the first 2 years of follow-up. Conclusion: ENKTL-NT is rare aggressive NHL subtype with good response to L-asparaginase-based chemotherapy sandwiched with radiation therapy. SMILE is a more toxic regime than AspaMetDex but can be managed with proper supportive care.